Pengaruh Penggunanan Instagram Terhadap Motivasi Belajar Siswa Pada Pembelajaran PAI (Tazakka: Jurnal Pendidikan dan Keislaman, 2024)
Current technological developments impact all aspects of life, including education. One such development is the use of Instagram, a social media platform widely used by students. This research aims to assess the level of Instagram usage among students at SMA N 1 Kinali and to determine the extent of learning motivation among 11th-grade students at the same school. Additionally, it seeks to explore the influence of Instagram usage on the learning motivation of these students. This study employs descriptive quantitative research methods, with a population of 300 students and a sample of 33 students selected using a non-random sampling technique. The data collected from respondents were analyzed using SPSS version 27 software. The results indicate that Instagram usage among 11th-grade students at SMA N 1 Kinali is frequent. However, based on the t-test results, the significance value is 0.145 > 0.05, and the R Square value is very low, at 0.067 or 6.7%. This suggests that the independent variable (Instagram usage) has no significant effect on the dependent variable (learning motivation), with the remaining influence attributable to other factors. Therefore, it can be concluded that Instagram usage does not significantly impact the learning motivation of 11th-grade students at SMA N 1 Kinali.
Keywords: Instagram Media; Learning Motivation; Islamic Religious Education